Genetic testing for a patient with suspected familial hypercholesterolaemia. (19th July 2018) - Mudgundi, Venugopal; Williams, Geoffrey; Manou, Katherine; Block, Robert
Abstract : Familial hypercholesterolaemia (FH) is a genetic condition that results in elevated low-density lipoprotein (LDL) cholesterol (LDL-C) levels with consequent increased risk for premature cardiovascular disease events. Although it is considered an autosomal-dominant genetic condition, the underlying genetic causes of FH can be complex. Currently most guidelines rely on clinical criteria to diagnose FH. But this approach has some pitfalls. We present a patient who was not formally diagnosed with FH using commonly used and well-accepted clinical criteria but via genetic testing was found to have a mutation for this disorder. This case brings to fore the challenges clinicians face in diagnosing and managing such unusual cases optimally. Through this case report, we hope to stimulate a debate among clinicians as well as other stakeholders regarding the need to develop more efficient ways of selecting patients for genetic testing in response to elevated LDL levels.